71.0k views
3 votes
Factor.

x2−5x+6

Enter your answer in the boxes.

x2−5x-6= ( ) ( )​

User AlokeT
by
6.5k points

1 Answer

5 votes

Answer:


(x-6)(x+1)

Explanation:

Factoring is usually just a bit of guess and check.
x^2-5x-6 is written in the form
a^2+b+c, where
a=1,
b=-5, and
c=-6.

You need to find the two numbers that multiply together to equal
-6 and can be added together to get
-5. These are
-6 and
1 in this case.

Now, put them together in the form
(x-6)(x+1). We will now check this answer using the FOIL method.

First term in each parentheses:
x * x = x^2

Outside terms:
x * 1 = x

Inside terms:
-6 * x = -6x

Last term in each parentheses:
-6 * 1 = -6

Now, add these together:
x^2 + x - 6x - 6 = x^2 - 5x - 6

Since we get the original expression, this is correct.

User Rahul Roshan
by
5.7k points